Numerical Investigation of Radiative Heat Transfer in a Particulate Medium Using FTn Finite Volume Method. (February 2019) - Moghadassian, Behnam; Jafari, Mohammad; Hafezisefat, Parinaz; Mirhosseini, Mojtaba; Rezania, Alireza
Abstract: Radiative heat transfer in participating medium finds applications in high temperature systems where the medium is not perfectly transparent. Examples are combustion chambers and layers of Earth's atmosphere. Presence of tiny particles (ranging from 500 nanometers to 10 micrometers in diameter) in a medium strongly affects the radiative heat transfer. The governing equations for solving the heat transfer in the medium are discretized using FT n finite volume method. The major step in simulating the radiative heat transfer in a particulate medium is finding the scattering phase function. The original Mie theory (without any approximation) is used to calculate scattering phase functions. Non-orthogonal mesh is applied to discretize the non-orthogonal computational domain. The intensities at cell faces are found by relating them to nodal values through the high resolution CLAM scheme. Cases of scattering in media with dielectric particles and absorbing particles are considered. Also, the influences of the particle density on the dimensionless radiative heat flux and direction-integrated intensity are studied.